(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Major burns lead to a hyper metabolic state that is more severe than any other disease or injury. Major burns increase the metabolic requirements of the body and due to severe catabolism can lead to severe loss of body weight, muscle loss, increased risk of infection, protein loss and mortality. Therefore, Careful nutritional assessment, adequate and timely provision of medical nutrition therapy is an essential component to meet the nutritional requirements in critically ill burn patient to reduce infection, recovery, long-term results and clinical outcomes. This case study focuses on aggressive nutritional care of adults with major burns.